Adapting the barrows model of moral education to the psychosocial needs of the Iranian education system - davood forootanzad; davood manavipoor; farhad ebizadeh (مجله علوم روانشناختی)
Background: The importance of moral education in schools is undeniable. Various models have been proposed for moral education in schools, one of which is the Baro Model of Moral Education based on Baro's theory. Some studies have shown that teachers generally support this model. However, some teachers have also expressed concerns about how to implement this model in the classroom. Despite the potential benefits of this model, there have been few studies on teachers' views of it. Aims: The aim of this research was to analyze teachers' views on the Baro Model of Moral Education and to adapt it to the psychosocial needs of the Iranian education system. Methods: The research method was qualitative and phenomenological. The statistical population included all teachers working in the city of Garmsar in the academic year 1402-1401 (2023-2024). 20 of them were selected purposefully and interviewed based on the entry criteria. Data were collected through semi-structured interviews and analyzed using Maxqda2022 software. Results: The findings showed that the five primary principles of Baro's theory, namely happiness with 7 sub-themes, truth with 5 sub-themes, freedom with 2 sub-themes, respect with 1 sub-theme, and fairness with 3 sub-themes, were approved and accepted by the participants. However, for each of the five principles, additional secondary principles were proposed by the participants in accordance with the educational context and conditions prevailing in the Iranian education system. Conclusion: In general, the results of this study can be inferred that all the primary and secondary principles in the Baro Model of Moral Education are approved by the participating teachers. Therefore, it is proposed that the stakeholders of the education system prepare the ground for the implementation of the Baro Model of Moral Education and the proposed modifications suggested by the participants. In this way, specialized seminars can be held to explain the principles of this moral model.